Analysis of the efficiency of the use of automated accounting software. (Journal of Economic Research & Business Administration, 2015)
The article analyzes the effectiveness of the use of automated accounting software. Considered the economic criteria that characterize software product from the cost-saving entry and use of software in the enterprise.